Entrevista a Lourdes Chau Quispe: Reflexiones y perspectivas en torno a las reformas tributarias en materia de procedimientos y procesos judiciales tributarios - Rodríguez Alzza, Efraín (2014)
In this interview, Dr. Chau shares some ideas about the tax reforms of the past two years and their implementation. In this way, the interview addresses the news that brought the introduction of partial audits, individual consultations and the procedures related to these. Then, it focuses on the role of the Tax Court in the implementation and consolidation of these new tax law institutions.